Evaluation of the groundwater quality in Pariya - Abubakar, Mahmoud Hijab; Z.A, Belel; Abba, Hadi A. (International Journal of Integrated Engineering, 2017)
Abstract: This article attempts to appraise the groundwater water quality of Pariya, Nigeria. Water samples was collected from 10 different borehole sources in the study area and analysed for the physicochemical factors such as pH, TDS, Total Hardness, Calcium, Magnesium, Sodium, Potassium, Chloride, Sulphate, Lead, Fluoride, Iron, Bicarbonate and total coliforms. The results of physicochemical quality was compared with the WHO standards. It was found that the physicochemical quality was within the permissible limits. The bacteriological analyses indicated the occurrence of total coliforms above the standards. It was recommended to adopt basic treatment by boiling before ingestion to safeguard against water borne diseases.